2018
DOI: 10.1080/10717544.2018.1516003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and imaging of miR-155 in the early screening of lung cancer by targeted delivery of octreotide-conjugated chitosan-molecular beacon nanoparticles

Abstract: Lung cancer is still the most common cancer globally. Early screening remains the key to improve the prognosis of patients. There is currently a lack of specific and sensitive methods for early screening of lung cancer. In recent years, studies have found that microRNA plays an important role in the occurrence and development of lung cancer and become a biological target in the early diagnosis of lung cancer. In this study, lung cancer cells, subcutaneous xenografts of lung cancer in nude mice, and Lox-Stop-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Notably, SphK1 promotes NSCLC development. Overexpression of SphK1 exacerbates the development of NSCLC by activating STAT3 [ 21 , 42–48 ]. Herein, LINC00960 sponged miR-124a to upregulate the expression of SphK1.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, SphK1 promotes NSCLC development. Overexpression of SphK1 exacerbates the development of NSCLC by activating STAT3 [ 21 , 42–48 ]. Herein, LINC00960 sponged miR-124a to upregulate the expression of SphK1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-155 exerts a cancer-promoting effect in the occurrence and development of multiple cancers. miR-155 is not only overexpressed in several cancers such as breast, colorectal, gastric, and liver cancers, but also increased abnormally in the tissues and serum of the lung cancer patients, thereby miR-155 is a potential molecular marker for the early diagnosis of lung cancer, Moreover, lung cancer patients with high expression of miR-155 have a short survival time and poor prognosis (Liu et al 2017;Zhu et al 2018). MB technology can implement a convenient, rapid, and dynamic detection of miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 has already been confirmed by previous studies to be of vital importance for the carcinogenesis and progression of diverse cancers, for instance, liver cancer, colorectal cancer, and gastric cancer [ 35–37 , 44 ]. Furthermore, miR-155-5p stimulates oxalate- and calcium-induced renal oxidative stress suffering by inhibiting MGP expression [ 45 ].…”
Section: Discussionmentioning
confidence: 71%